Flow Interrupted: A Marxist Analysis of Tradition, Identity, and Displacement in Titas Ekti Nadir Naam: Aliran yang Terputus: Analisis Marxis tentang Tradisi, Identitas, dan Pengungsian dalam “Titas Ekti Nadir Naam” - Sikder, Sumon (Journal of Literature and Education, 2025)
Adwaita Mallabarman’s Titas Ekti Nadir Naam explores the disruption of tradition, identity, and space in a rural Bengali community. The study applies a Marxist-Cultural Studies approach to examine how economic and cultural changes affect the community. Marxist theory highlights the class struggles and material conditions that lead to the exploitation of the rural poor. This causes the breakdown of the socio-economic structure and disrupts the cultural continuity tied to the river. Cultural Studies examines how the community’s cultural identity and narratives are challenged by external forces like colonialism, capitalism, and modernization. These forces distort the cultural fabric, causing a crisis of identity and displacement. The relationship between material conditions and cultural identity is crucial. It shows the tension between economic oppression and cultural resistance. The objective is how economic and cultural shifts, specifically capitalism and modernization, disrupt the identity, tradition, and socio-economic fabric of the Malo community. It focuses on how the river’s flow, symbolizing life and continuity, is ‘interrupted’ by modernity and colonialism. This leads to both material and cultural disintegration. By combining Marxist and Cultural Studies perspectives, the research reveals the complex dynamics of class, culture, and identity in a changing world.